MO055THE IMPACT OF THE COVID-19 PANDEMIC ON MOOD STATUS AND TREATMENT ADHERENCE IN PATIENTS WITH FABRY DISEASE. (29th May 2021) - Dincer, Mevlut Tamer; Karaca, Cebrail; Sarac, Betul; Ahmadzada, Saffa; Bakir, Alev; Alagoz, Selma; Kiykim, Ertugrul; Trabulus, Sinan; Seyahi, Nurhan
Abstract: Background and Aims: Fabry disease is a rare metabolic disorder, lifelong enzyme replacement therapy with recombinant human alpha-galactosidase A (agalsidase) constituted the cornerstone of disease-specific therapy. COVID-19 pandemic and epidemic control measures including lockdowns impaired access to health care services. We examined the effect of COVID-19 pandemic and lockdown measures on mood status and management of Fabry disease patients. Method: We conducted a cross-sectional study between October 2020 and December 2020. We used the Hospital Anxiety and Depression Scale (HADS) to evaluate the mood statuses of FD patients and the Morisky Medication Adherence Scale (MMAS-4) to assess patient adherence. We also examined age and sex-matched control group to compare mood status. Results: A total of 68 (Male 48.5 %, mean age 37.0) FD patients were under regular follow-up in our institution, 59 of those patients were taking ERT every other week. Two of our patients had reported having a COVID-19 infection, and both of them recovered. 25 patients reported to miss an ERT for a median of one dose, 16 of these 25 patients have reported that they did not come to the hospital because of infection fear. Half of the patients had adopted home-based infusion; they arranged a nurse for home-based infusion therapy by their own means. According to MMAS-4 FD patients had good adherence to their therapy (Median score 0, range 0-2). Mood status of FD patients and controls are shown in Table 1 . Both HADS depression and anxiety scores were higher in the control group compared to FD patients. Additionally, abnormal scores were more prevalent for HADS depression scores in controls (Figure 1 ). Conclusion: We found that the mood status of FD patients was better than the control group. Traumatic growth may be an important factor to explain this finding. Their adherence to therapy was good. Home-based therapy was the preferred method by the patients. Government-supported home therapy programs might be beneficial for FD patients to increase adherence to the therapy.